A comparative study of the genre of cursing in Uzbek and Russian - Zokirova Dilrabo Khaydarovna (Research Parks Publishing LLC, 2021)
This article provides a theoretical overview of the content of curses, one of the examples of folklore, and a comparative study of Russian and Uzbek languages.